2018
DOI: 10.3389/fmicb.2018.02252
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antifungal Compounds, Spermine-Like and Short Cyclic Polylactates, Produced by Lactobacillus harbinensis K.V9.3.1Np in Yogurt

Abstract: Lactobacillus harbinensis K.V9.3.1Np was described as endowed with high antifungal activity. Most of the studies associated this activity to the produced organic acids, i.e., lactic acid, acetic acid, and hexanoic acid. The aim of this study was to purify and identify, other not yet described, antifungal molecules produced by L. harbinensis K.V9.3.1Np when used in yogurt fermentation. Active compounds were extracted through several extraction processes using organic solvents and protein precipitation. The frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…There has been great progress in understanding and exploring novel antifungal metabolites of LAB during the last few years. Apart from some novel antifungal peptides produced by many LAB species (Gerez, Torres, Font de Valdez, & Rollán, 2013;Luz et al, 2017;McNair et al, 2018;Muhialdin et al, 2016;Muhialdin, Hassan, & Saari, 2018;Rather et al, 2013), many other novel antifungal metabolites of LAB have been reported recently that included 10-hydroxy-12-octadecenoic acid (10-HOE), 13-hydroxy-9-octadecenoic acid (Chen, Liang, Curtis, & Ganzle, 2016), benzeneacetic acid, 2-propenyl ester (Wang, Yan, Wang, Zhang, & Qi, 2012), phenolic antioxidants (such as, 2,4 di-tert-butyl phenol) (Sellamani et al, 2016;Varsha et al, 2015), 2-hydroxy-(4-methylthio) butanoic acid, 2-hydroxy-3-methylbutanoic (Honoré et al, 2016) and spermine-like and short cyclic polylactates (Mosbah et al, 2018). Aunsbjerg et al (2015) reported the role of volatile compounds (diacetyl) produced by Lactobacillus paracasei DGCC 2132 in inhibiting the growth of two fungal species belonging to the genus Penicillium: P. solitum DCS 302 and Penicillium sp.…”
Section: Metabolites Of Lab To Retard Fungal Growthmentioning
confidence: 99%
“…There has been great progress in understanding and exploring novel antifungal metabolites of LAB during the last few years. Apart from some novel antifungal peptides produced by many LAB species (Gerez, Torres, Font de Valdez, & Rollán, 2013;Luz et al, 2017;McNair et al, 2018;Muhialdin et al, 2016;Muhialdin, Hassan, & Saari, 2018;Rather et al, 2013), many other novel antifungal metabolites of LAB have been reported recently that included 10-hydroxy-12-octadecenoic acid (10-HOE), 13-hydroxy-9-octadecenoic acid (Chen, Liang, Curtis, & Ganzle, 2016), benzeneacetic acid, 2-propenyl ester (Wang, Yan, Wang, Zhang, & Qi, 2012), phenolic antioxidants (such as, 2,4 di-tert-butyl phenol) (Sellamani et al, 2016;Varsha et al, 2015), 2-hydroxy-(4-methylthio) butanoic acid, 2-hydroxy-3-methylbutanoic (Honoré et al, 2016) and spermine-like and short cyclic polylactates (Mosbah et al, 2018). Aunsbjerg et al (2015) reported the role of volatile compounds (diacetyl) produced by Lactobacillus paracasei DGCC 2132 in inhibiting the growth of two fungal species belonging to the genus Penicillium: P. solitum DCS 302 and Penicillium sp.…”
Section: Metabolites Of Lab To Retard Fungal Growthmentioning
confidence: 99%
“…The investigations of novel antifungal compounds and compounds having a synergistic effect on antifungals have been increasing in recent decades [1][2][3][4]. Approximately 215 fungicides have been sorted based on their mode of action (MOA) in the biochemical pathways of plant fungal pathogens in the Fungicide Resistance Action Committee (FRAC) MOA Code List 2019 [1].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, both L. plantarum and related low-molecular-weight substances showed significant antifungal activity [70]. Recent research revealed that various novel metabolites of LAB, including 13-hydroxy-9-octadecenoic acid, 10-hydroxy-12-octadecenoic acid [71], phenolic antioxidants [72], and spermine-like and short cyclic polylactates [73], showed lower minimum inhibitory concentrations of mycotoxins compared to the ordinary organic acids. Lactobacillus fermentum YML014 was also shown to reduce A. flavus by up to 50% after isolation from Nigerian fermented food (Cassava) [74].…”
Section: Biocontrol Methodsmentioning
confidence: 99%